Context Mapping for Integrated Urban Development in Nepal: A Case Study of Aathbiskot Municipality, Rukum (Research Nepal Journal of Development Studies, 2018)
The world is undergoing the largest wave of urban growth in history, particularly since 1950s that accelerated further after 2000s. However, Nepal is experiencing a new political system of federalism, it is yet to be equipped with appropriate Acts and policies to foster the spirit of development and constitution at large. In this context, the present study sets a research question as of how a context mapping can be done before integrated urban planning of the municipalities. Methodologically, the study was conducted in Aathbiskot municipality of Rukum district. Involving both qualitative and qualitative techniques under the social constructivist epistemological position, the study was conducted on the basis of participatory approach through analytical methods, including SWOT analysis, Trend analysis, Ward analysis and Linkage analysis. The findings show that as an aspiring city, Aathbiskot Municipality has diverse prospects and sectors of development that would drive its future growth but identifying some lead sectors and potential development opportunity of the municipality based on its own strength and individuality would what make municipality grow better and prosper. The study strongly claims inferences for the homogeneity in the long-term vision setting, however, maintaining through heterogeneity in the specific plans and strategies for the different wards of the municipality.